2019
DOI: 10.3390/rs12010004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Small-Footprint Airborne Lidar-Derived Estimates of Gap Probability and Leaf Area Index

Abstract: Airborne lidar point clouds of vegetation capture the 3-D distribution of its scattering elements, including leaves, branches, and ground features. Assessing the contribution from vegetation to the lidar point clouds requires an understanding of the physical interactions between the emitted laser pulses and their targets. Most of the current methods to estimate the gap probability (P gap ) or leaf area index (LAI) from small-footprint airborne laser scan (ALS) point clouds rely on either point-number-based (PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Most studies suggested that PNB LPIs are superior to IB LPIs for DALS PCD [33,51]. The use of IB LPIs remains a controversial issue due to the unclear physical meaning of intensity and difficulty in performing intensity correction [1,21,42,53,54].…”
Section: Lpis Formmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies suggested that PNB LPIs are superior to IB LPIs for DALS PCD [33,51]. The use of IB LPIs remains a controversial issue due to the unclear physical meaning of intensity and difficulty in performing intensity correction [1,21,42,53,54].…”
Section: Lpis Formmentioning
confidence: 99%
“…The empirical method was also highly sensitive to tree age, time, stand density, the accuracy of field measurement data of LAI, etc. [53,55,57,82]. Overall, all regression models are calibrated and validated against local field data; however, reliable models that can be transferred to other locations, times, and different LiDAR systems are unfortunately lacking [21,53].…”
Section: Empirical Regression Based On Proxy Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaves with a square shape and an area of 0.05×0.05 m 2 (used in [42]) were randomly distributed within cylindrical, spherical, and conical tree crowns. We generated six different values of Leaf Area Density (ρ, unit: m 2 /m 3 ), the one-sided leaf area per volumetric unit [43], ranging from 0.25 to 1.50 (the ρ used in previous studies ranges from 0.25 to 1.59 [35], [42], [44], [45]) with an increment of 0.25. Both sides of the leaf surface and the ground were all set to bi-Lambertian.…”
Section: ) Abstract Discontinuous Canopiesmentioning
confidence: 99%
“…Techniques utilizing remote sensing to retrieve LAI can be divided into three categories according to the platform: 1) ground-based measurement, 2) airborne observation, and 3) satellite observation [5][6][7][8]. As the most accurate measurement of forest LAI, ground-based measurement is usually used to verify the LAI inversion of higher platforms (e.g., airborne or spaceborne) [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%